HIV immunological non-responders are characterized by extensive immunosenescence and impaired lymphocyte cytokine production capacity - Vos, Wilhelm A. J. W.; Navas, Adriana; Meeder, Elise M. G.; Blaauw, Marc J. T.; Groenendijk, Albert L.; van Eekeren, Louise E.; Otten, Twan; Vadaq, Nadira; Matzaraki, Vasiliki; van Cranenbroek, Bram; Brinkman, Kees; van Lunzen, Jan; et al. (Frontiers in Immunology, 2024)
Introduction: Immunological non-responders (INR) are people living with HIV (PLHIV) who fail to fully restore CD4+ T-cell counts despite complete viral suppression with antiretroviral therapy (ART). INR are at higher risk for non-HIV related morbidity and mortality. Previous research suggest persistent qualitative defects. Methods: The 2000HIV study (clinical trials NTC03994835) enrolled 1895 PLHIV, divided in a discovery and validation cohort. PLHIV with CD4 T-cell count <350 cells/mm 3 after ≥2 years of suppressive ART were defined as INR and were compared to immunological responders (IR) with CD4 T-cell count >500 cells/mm 3 . Logistic and rank based regression were used to analyze clinical data, extensive innate and adaptive immunophenotyping, and ex vivo monocyte and lymphocyte cytokine production after stimulation with various stimuli. Results: The discovery cohort consisted of 62 INR and 1224 IR, the validation cohort of 26 INR and 243 IR. INR were older, had more advanced HIV disease before starting ART and had more frequently a history of non-AIDS related malignancy. INR had lower absolute CD4+ T-cell numbers in all subsets. Activated (HLA-DR+, CD38+) and exhausted (PD1+) subpopulations were proportionally increased in CD4 T-cells. Monocyte and granulocyte immunophenotypes were comparable. INR lymphocytes produced less IL-22, IFN-γ, IL-10 and IL-17 to stimuli. In contrast, monocyte cytokine production did not differ. The proportions of CD4+CD38+HLA-DR+ and CD4+PD1+ subpopulations showed an inversed correlation to lymphocyte cytokine production. Conclusions: INR compared to IR have hyperactivated and exhausted CD4+ T-cells in combination with lymphocyte functional impairment, while innate immune responses were comparable. Our data provide a rationale to consider the use of anti-PD1 therapy in INR.